2015
DOI: 10.1002/cite.201400095
|View full text |Cite
|
Sign up to set email alerts
|

Ion‐Exchange Adsorption of Proteins: Experiments and Molecular Dynamics Simulations

Abstract: The adsorption of serum albumin and hemoglobin onto Q Sepharose FF was investigated, where the single and binary adsorption were considered. Both experiments and molecular dynamics simulations have been performed to study the adsorption from macroscopic and microscopic points of view. The steric mass-action model was applied to describe the single adsorption isotherms and to predict the binary isotherms. The results of the experiments and simulations were connected and compared by two parameters of the steric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…10 Some studies can be found in the literature based on ion exchange for protein adsorption and separation, such as the adsorption of bovine serum albumin, ovalbumin, and conalbumin on a strong anion exchanger by Field et al with measurement of the adsorption equilibrium isotherms for multicomponent mixtures, 11 while the adsorption of serum albumin and hemoglobin with the anion exchanger Q Sepharose FF was studied by Liang et al and the SMA model was implemented to describe the adsorption equilibrium. 12 Noh et al also studied the adsorption of three proteins, lysozyme, human serum albumin, and immunoglobulin G, on anion and cation exchangers. 13 There are also some studies regarding the evolution of protein concentration during adsorption experiments on ion exchangers.…”
Section: Introductionmentioning
confidence: 99%
“…10 Some studies can be found in the literature based on ion exchange for protein adsorption and separation, such as the adsorption of bovine serum albumin, ovalbumin, and conalbumin on a strong anion exchanger by Field et al with measurement of the adsorption equilibrium isotherms for multicomponent mixtures, 11 while the adsorption of serum albumin and hemoglobin with the anion exchanger Q Sepharose FF was studied by Liang et al and the SMA model was implemented to describe the adsorption equilibrium. 12 Noh et al also studied the adsorption of three proteins, lysozyme, human serum albumin, and immunoglobulin G, on anion and cation exchangers. 13 There are also some studies regarding the evolution of protein concentration during adsorption experiments on ion exchangers.…”
Section: Introductionmentioning
confidence: 99%